Opening and Changes of the Firms TIC: Case of Cuts Internet in Political Matter in Democratic Republic of Congo - (:unkn) unknown (My University, 2019)
The cuts of Internet in political matter started with "Arab spring" and since then know a fast progression in Africa at the point to become an international public problem today putting in scene the modes in place, in certain African States, and their opponents. Indeed, in what appears as a battle for the control of information and the control of the public opinion, there are on a side the African governments which, to justify the interruption of Internet, propose the need for safeguarding of the law and order like act of sovereignty, in fact the right to prevent the misinformation and any illegal publication of the electoral data. On the other side, there are the oppositions which view this step as the violation of the principles of freedoms, in particular the freedom of expression, at ends of fiddle of the electoral data. The scientific stake of this analysis, starting from African case studies, and of the RDC in particular, is to reflect on the ambivalence of the decision to cut Internet, in order to as well show the consequences of these restrictions on the economy, the credibility of the elections, the social one and, by the same occasion, to carry a glance on the reaction of the international community.
Keywords: African Research